Growth performance, blood profiles and egg production of Coturnixjaponica (Temm Inck and Schlegel, 1849) fed diets supplemented with Tithonia diversifolia a. gray leaves (2020)
This study investigated the growth performances, egg production and blood profiles of Coturnix japonica fed concentrate diets supplemented with Tithonia diversifolia leaf meal (TDLM). One hundred (two-week old) C. japonica chicks were allocated to five dietary treatments. The experimental birds were allowed to acclimatize for one week, before feeding trials lasted for twelve weeks. Diets were formulated with TDLM inclusions at 0 % (A), 2.5% (B), 5 % (C), 7.5% (D) and 10 % (E) to the standard dietary formulations. Diets and water were provided for the chicks, ad-libitum. Data collected on growth performance, blood profiles, serum biochemistry and egg production, were analyzed using descriptive and inferential statistics. Inclusion of TDLM had a significant influence on growth performance, blood profiles, and egg production (P<0.05). After 12 weeks, Diet C had the highest body weight (148.37 ± 0.76 g), while control diet had least (144.93 ± 1.05 g). The control diet had 20% mortality, while Diet D had 5% mortality due to injuries from other birds' attack. Egg weight varied from 9.60 ± 0.14 g (control) to 11.39 ± 0.12 g (Diet E). The blood profiles responded positively to TDLM inclusion with the birds developing stronger immunity when compared to those fed the control diet. Serum biochemistry did not significantly differ indicating that there were no negative effects due to TDLM inclusion. TDLM at 2.5 and 5.0 % inclusions had the highest positive effects on growth performance, haematological parameters, egg production and serum biochemistry of the quails.